Tingkat pengetahuan mahasiswa semester VI, Pogram Studi Pendidikan Dokter, Fakultas Kedokteran, Universitas Udayana terhadap konjungtivitis bakteri tahun 2017 - I Made Gede Dwipayana Putra; Putu Budhiastra; Ni Ketut Niti Susila (Intisari Sains Medis, 2019)
Bacterial conjunctivitis is an infection of the eye caused by bacteria, such as Staphylococcus, Streptococcus, or Haemophilus. Based on 30% of visits in the Department of Eye Disease in the United States, 15% are conjunctivitis complaints caused by bacteria and virus, and 15% are conjunctivitis complaints caused by allergy. A common complication of conjunctivitis is the decreased visual acuity that greatly affects the patient in performing daily activities.Aim: This study aimed to determine the knowledge level of semester VI students of Doctor Education Study Program, Faculty of Medicine, Udayana University, toward conjunctivitis.Method: The samples were 70 people with 10% relative accuracy. Sampling was done by random sampling technique. The data were collected by using questionnaire technique. Data analysis was performed using descriptive statistics.Result: The result of the students' knowledge level on bacterial conjunctivitis was 62 respondents (89%) were in good category, 8 respondents (11%) were in moderate category, and none for poor category (0) as well. The knowledge level of the respondent toward bacterial conjunctivitis at the age of 21 years was quite good, that were 31 people (44.5%). Respondents with moderate knowledge level at the age of 21 years were 5 people.Conclusion: The result of the test shows that the level of students' knowledge on bacterial conjunctivitis is that 62 respondents (89%) are in good category. Therefore, to the management of Faculty of Medicine, Udayana University, this research is expected to be used as a reference in formulating various learning strategies, so the learning achievement can be improved.